Third molar comparison in extraction and nonextraction orthodontic cases - Peña, Danelin (2019)
Introduction: This study aimed to compare the third molars angulation and eruption status in Class I and II malocclusions in orthodontic treatment with and without first premolar extractions. Methods: The sample was comprised by 96 patients divided into four groups: Group 1 Class I malocclusion treated with first premolars extraction; Class I malocclusion treated without extractions; Group 3 Class II malocclusion treated with first premolars extraction; Group 4 Class II malocclusion treated without extractions. Panoramic radiographs were used to evaluate third molars mesiodistal angulations at T1, T2 and at T3. Third molar eruption status was assessed in dental casts. Intergroup angulations and eruption status comparisons were performed using ANCOVA followed by Tukey tests and Kruskal-wallis test, respectively. Results: Significantly greater mesial angulation and percentage of erupted right maxillary third molars were found in Class I extraction group. Significantly greater distal angulation and percentage of erupted right mandibular third molars were found in Class II extraction group. Conclusion: Class I and II extraction treatment exhibited more favorable angulations and greater number of erupted third molars than nonextraction treatment. Regardless the treatment performed third molars showed a more uprighted position in each malocclusion type.